INTEGERS 13 (2013) #A75 AN EXPLICIT FORMULA FOR HIGHER ORDER BERNOULLI POLYNOMIALS OF THE SECOND KIND Haiqing Wang Dept. of Mathematics, Huizhou University, Huizhou, Guangdong, P. R. China Guodong Liu1 Dept. of Mathematics, Huizhou University, Huizhou, Guangdong, P. R. China gdliu@pub.huizhou.gd.cn Received: 3/15/13, Accepted: 11/5/13, Published: 11/27/13 Abstract In this paper, the authors establish a formula expressing the Bernoulli polynomials (k) of the second kind and general order k, bn (x), in terms of those of first order, (1) bn (x) = bn (x). 1. Introduction and Results (k) The Bernoulli polynomials bn (x) of the second kind and of order k, for any integer k, may be defined by (see [2,4,10]) ✓ t log(1 + t) (k) ◆k (1 + t)x = 1 X n b(k) n (x)t , n=0 |t| < 1. (1) (k) The numbers bn = bn (0) are the Bernoulli numbers of the second kind and (1) (1) of order k; bn = bn , bn (x) = bn (x) are the ordinary Bernoulli numbers and polynomials of the second kind (see [1,4,5, 10-13]), and Cn = n!bn are the Cauchy numbers of the first kind (see [8, 13]). By (1.1), we have X b(k) bv1 (x/k)bv2 (x/k) · · · bvk (x/k), (2) n (x) = v1 ,··· ,vk 2N0 v1 +···+vk =n b(k) n = X v1 ,··· ,vk 2N0 v1 +···+vk =n 1 Corresponding author. bv1 bv2 · · · bvk , (3) 2 INTEGERS: 13 (2013) and b(k) n (x) = (k) b0 ✓ ◆ ✓ ◆ ✓ ◆ x x x (k) (k) + b1 + · · · + bn 1 + b(k) n . n n 1 1 (4) where n 2 N0 = N [ {0}, N being the set of positive integers. The numbers bn satisfy the recurrence relation (see [1, 5]) n X b0 = 1, j=0 ( 1)j bj = 0 (n n j+1 1), (5) 1 1 19 3 863 so we find b1 = 12 , b2 = 12 , b3 = 24 , b4 = 720 , b5 = 160 , b6 = 60480 . The numbers bn satisfy many interesting relations. For example (see [1,5,8]) bn = Z 1 0 ✓ ◆ x dx, n 1 X |bn | log 2 = , n +1 n=1 1 X |bn |Hn ⇡2 1+ = , n 6 n=1 (6) Pn is the Euler constant and Hn = k=1 k1 is the 1 1 X |bn | = , n n=1 2)···(x n+1) where nx = x(x 1)(x n! , n-th harmonic number. (k) The Bernoulli polynomials Bn (x) of order k, for any integer k, may be defined by (see [3,4,6,7,10]) ✓ t et 1 (k) ◆k ext = 1 X Bn(k) (x) n=0 tn , n! |t| < 2⇡. (7) (k) (1) The numbers Bn = Bn (0) are the Bernoulli numbers of order k, and Bn = Bn (n) are the ordinary Bernoulli numbers. The numbers Bn are called Nörlund numbers (see [3]), or Cauchy numbers of the second kind (see [8, 13]). Nörlund found the exponential generating function (see [10, p.150]) 1 X t tn = Bn(n) (1 + t) log(1 + t) n=0 n! (k) (n) These numbers bn , bn , Bn (see [1-4]) n!bn = Bn(n) + (n 1) nBn 1 , Bn(n) (k) and Bn (8) satisfy various identities. For example n X = n! ( 1)n j=0 (|t| < 1). j bj , and n!b(k) n = k k n Bn(n k) . (9) The paper’s central result is a formula expressing the Bernoulli polynomials of (k) the second kind and general order k, bn (x), in terms of those of first order, bn (x) = (1) bn (x). That is, we shall prove the following main conclusion. 3 INTEGERS: 13 (2013) Theorem. Let n, k 2 N and n ( 1)k 1 (k k)!b(k) n (x) = 1)!(n 1. Then k X1 (n 1 j)! j=0 X ⇥ k (n j 1 x)v1 (n j v1 ,··· ,vk j 2N0 v1 +···+vk j =j 2 x)v2 · · · (n k x)vk j bn j (x). (10) By taking x = 0 in Equation (10), we can deduce the following. Corollary 1. Let n, k 2 N and n ( 1)k = 1 k X1 (k (n j=0 1)!(n 1 j)! k 1. Then j 1)v1 (n k)!b(k) n X v1 ,··· ,vk j 2N0 v1 +···+vk j =j (n j 2)v2 · · · (n k)vk j bn j. (11) Taking k = 2, 3, 4 in (10) and (11), we immediately deduce the following expressions for the first few higher order Bernoulli polynomials and numbers of the second kind: b(2) n)bn (x) + (x + 2 n)bn 1 (x) (n 1); n (x) = (1 1 b(3) 1)(n 2)bn (x) n (x) = (n 2 1 1 + (n 2)(2n 5 2x)bn 1 (x) + (n 3 x)2 bn 2 (x) (n 2); 2 2 1 1 b(4) (n 1)(n 2)(n 3)bn (x) (n 2)(n 3)(3n 9 3x)bn 1 (x) n (x) = 6 6 1 (n 3) (n 3 x)2 + (n 3 x)(n 4 x) + (n 4 x)2 bn 2 (x) 6 1 (n 4 x)3 bn 3 (x) (n 3); 6 b(2) n)bn + (2 n)bn 1 (n 1); n = (1 1 1 1 b(3) 1)(n 2)bn + (n 2)(2n 5)bn 1 + (n 3)2 bn 2 (n 2); n = (n 2 2 2 1 1 (4) bn = (n 1)(n 2)(n 3)bn (n 2)(n 3)(3n 9)bn 1 6 6 1 1 (n 3) (n 3)2 + (n 3)(n 4) + (n 4)2 bn 2 (n 4)3 bn 3 6 6 (n 3). 4 INTEGERS: 13 (2013) By (11), (3), and noting that Cn = n!bn , we obtain an explicit formula for the sum involving Cauchy numbers of the first kind: ( 1)k 1 (k 1)!(n X k)! Cv1 Cv2 · · · Cvk v1 !v2 ! · · · vk ! v1 ,··· ,vk 2N0 v1 +···+vk =n = k X1 X (n 1)v1 (n j 2)v2 · · · (n j j=0 v1 ,··· ,vk j 2N0 v1 +···+vk j =j k)vk j Cn j . (12) n j Corollary 2. Let n, k 2 N0 and m 2 N. Then ( 1)k k! Z m 0 X ⇥ b(k) n (x)dx = n+1 X✓ i=1 (n v1 i ◆ k m X (n i j=0 (n j) (n i i i j)! k)! 1)v2 · · · (n j v1 ,··· ,vk+1 j 2N0 v1 +···+vk+1 j =j k)vk+1 j bn+1 i i j. (13) By taking m = 1 in (13), we can deduce the following: k ( 1) k!(n k 1)! Z 0 ⇥ X (n j 1 b(k) n (x)dx k X = (n 1 j)! j=0 1)v1 (n 2)v2 · · · (n j v1 ,··· ,vk+1 j 2N0 v1 +···+vk+1 j =j k 1)vk+1 j bn (0) Taking k = 0, 1; m = 1, 2, 3 in (13) and noting that bn (x) = Z 0 1 ✓ ◆ x dx = bn , n Z 0 2 ✓ ◆ x dx = 2bn + bn n Z 1, 3 0 x n j. (14) , we have ✓ ◆ x dx = 3bn + 3bn n 1 + bn and Z 1 bn (x)dx = (1 n)bn + (2 n)bn 1, 0 Z 2 bn (x)dx = 2(1 n)bn + 3(2 n)bn 1 + (3 bn (x)dx = 3(1 n)bn + 6(2 n)bn 1 + 4(3 n)bn 2, 0 Z 0 3 n)bn 2 + (4 n)bn 3. 2. 5 INTEGERS: 13 (2013) 2. Proof of Theorem In this section, we shall complete the proof of the theorem. First, the following lemma (see [2,10]) is crucial to the proof of the theorem. To be more self-contained, we present a simpler proof here. Lemma. Let n, k 2 N0 and m 2 N. Then b(k+1) (x) = n n k (k) n bn (x) + k k 1 x k (k) bn 1 (x). (15) Proof. By (1), we have 1 X (n n=0 = n k 1 k)b(k) n (x)t k ✓ 1 log(1 + t) ◆k+1 d = dt ✓ (1 + t)x ◆k 1 (1 + t)x log(1 + t) ✓ ◆k 1 1 +x (1 + t)x log(1 + t) 1 , (16) i.e., 1 X (n n=1 = kt (k) k ✓ 1)bn 1 log(1 + t) n k 1 1 (x)t ◆k+1 (1 + t)x + xt ✓ (n k 1 1 log(1 + t) ◆k (1 + t)x 1 . (17) By (16) and (17), we have 1 X (n n=0 = = n k 1 k)b(k) n (x)t + 1 X (k) 1)bn n k 1 1 (x)t n=1 ✓ ◆k+1 ✓ ◆k 1 1 x k (1 + t) + x (1 + t)x log(1 + t) log(1 + t) 1 1 X X n k 1 n k k b(k+1) (x)t + x b(k) . n n (x)t n=0 Comparing the coefficient of tn b(k+1) (x) = n (18) n=0 n k 1 on both sides of (18), we get k (k) n b (x) + k n k 1 k x (k) bn 1 (x). This proves the lemma. Now we complete the proof of the theorem by using mathematical induction and the method of coefficients (see [9]). 6 INTEGERS: 13 (2013) Proof of theorem. First note that (10) holds for k = 1, 2, by (15). Now suppose (10) is true for some natural number k and all n k 1. By superposition of (15), we have ( 1)k k!(n = ( 1)k = k X1 1 (n j=0 1)!b(k+1) (x) n k (k 1)!(n 1 1 x)v1 (n j 2 x)v2 · · · (n k x)vk (k (n j 1 v1 ,··· ,vk j 2N0 v1 +···+vk j =j +(n k 1 x) k X1 (n 2 k X1 (n j=0 ⇥ (n ⇥ 2 x)v1 (n j 3 x)v2 · · · (n k 1 1 k X j=0 X (n k 1 x) ⇥ X x)bn 1 (x) j bn j (x) x)vk j 1 x)v1 (n j 2 x)v2 · · · (n k x)vk j bn 1 j (x) k X (n 1 j bn j (x) j)! j=1 X (n (k) 1 j)! (n j 1 x)v1 (n j 2 v1 ,··· ,vk+1 j 2N0 v1 +···+vk+1 j =j 1 = k j v1 ,··· ,vk j 2N0 v1 +···+vk j =j +(n 1)!(n j)! v1 ,··· ,vk j 2N0 v1 +···+vk j =j = k j=0 X ⇥ 1)!(n j)! X ⇥ k k)!b(k) n (x) + ( 1) 1 x)v2 · · · (n k x)vk+1 1 j bn j (x) j)! (n j 1 x)v1 (n j 2 v1 ,··· ,vk+1 j 2N0 v1 +···+vk+1 j =j x)v2 · · · (n k 1 x)vk+1 j bn j (x), which shows that (10) is also true for the natural number k +1. The theorem follows by induction. 2 Now we complete the proof of Corollary 2. Proof of Corollary 2. By (11), (4), and noting that d (k) dx bn (x) (k 1) 1 (x) = bn (see [11]), 7 INTEGERS: 13 (2013) we have k ( 1) k! Z m b(k) n (x)dx 0 = n+1 X✓ i=1 ⇥ ⇣ (k+1) = ( 1) k! bn+1 (m) k ◆ k m X (n i j)! i j=0 (n i k)! X (n i j)v1 (n v1 ,··· ,vk+1 j 2N0 v1 +···+vk+1 j =j i j (k+1) bn+1 ⌘ k = ( 1) k! 1)v2 · · · (n n+1 X✓ i=1 i ◆ m (k+1) b i n+1 i k)vk+1 j bn+1 i j. This completes the proof. Acknowledgement. The authors would like to thank the referee for his/her very useful suggestions. This work was supported by the Guangdong Provincial Natural Science Foundation (No. 8151601501000002). References [1] T. Agoh and K. Dilcher, Recurrence relations for Nörlund numbers and Bernoulli numbers of the second kind, F ibonacci Quart. 48.1 (2010), 4-12. [2] L. Carlitz, A note on Bernoulli and Euler polynomials of the second kind, Scripta M ath. 25 (1961), 323-330. (n) [3] F. T. Howard, Nörlund’s number Bn , Applications of F ibonacci N umbers, Volume 5, Dordrecht: Kluwer, 1993, pp. 355-366. [4] F. T. Howard, Congruences and recurrences for Bernoulli numbers of higher order, F ibonacci Quart. 32 (1994), 316-328. [5] C. Jordan, Calculus of Finite Di↵erences, New York: Chelsea, 1965. [6] G.-D. Liu, Some computational formulas for Nörlund numbers, F ibonacci Quart. 45 (2007), 133-137. (x) [7] G.-D. Liu and H. M. Srivastava, Explicit formulas for the Nörlund polynomials Bn Comput. M ath. Appl. 51 (2006), 1377-1384. (x) and bn , [8] D. Merlini, R. Sprugnoli and M. C. Verri, The Cauchy numbers, Discrete M ath. 306 (2006), 1906-1920. [9] D. Merlini, R. Sprugnoli and M. C. Verri, The method of coefficients, Amer. M ath. M onthly 114 (2007), 40-57. [10] N. E. Nörlund, Vorlesungenüber Di↵erenzenrechnung, Springer-Verlag, Berlin 1924; Reprinted by Chelsea Publishing Company, Bronx, New York, 1954. [11] T. R. Prabhakar, Sharda Gupta, Bernoulli polynomials of the second kind and general order, Indian J. pure appl. M ath. 11 (1980), 1361-1368. [12] M. Wu and H. Pan, Sums of products of Bernoulli numbers of the second kind, F ibonacci Quart. 45 (2007), 146-150. [13] F.-Z. Zhao, Sums of products of Cauchy numbers, Discrete M ath. 309 (2009), 3830-3842.